Presence of Biosynthetic Gene Clusters (NRPS/PKS) in Actinomycetes of Mangrove Sediment in Semarang and Karimunjawa, Indonesia: 10.32526/ennrj/19/202100050 - Anggelina, Amelia Cahya; Pringgenies, Delianis; Setyati, Wilis Ari (Environment and Natural Resources Journal, 2021)
Actinomycetes are a group of bacteria that are widely distributed in soil, litter, water, and other natural sources. These Gram positive bacteria can produce hundreds of bioactive compounds, especially antibiotics. This research isolated culturable actinomycetes from mangrove sediments in the Semarang and Karimunjawa Island areas. The isolates that produce potential antibacterial compounds were identified by qualitative screening using the Biosynthetic Gene Cluster (NRPS/PKS) prediction approach. This research was conducted from June to November 2020. A total of 19 actinomycetes from Semarang and 17 actinomycetes from Karimunjawa were found to have at least one type of Biosynthetic Gene Cluster (NRPS, Type I or Type II PKS), but only three isolates had antibacterial activity against S. aureus, E. coli, and L. monocytogenes. Molecular identification found that the bacteria were similar to Brachybacterium paraconglomeratum (99.92%), Streptomyces pluripotens (100%), and Micromonospora chersina (99.08%). Results of the study concluded that the three bacterial isolates that had bacterial activity have similar genes with known antibiotic-producing genes and can potentially provide new antibiotic candidates.